2023
DOI: 10.1111/jocd.15661
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of superficial micro‐focused ultrasound with visualization for melasma in Asians: An uncontrolled pilot study

Abstract: Background The pathophysiology of melasma is multifactorial, resulting in treatment resistance and a high recurrence rate. Recent research suggests that focused ultrasound might treat melasma effectively. Objectives To investigate the efficacy and safety of superficial micro‐focused ultrasound with visualization (MFU‐V) for melasma in Asians. Methods Patients (n = 20) with mixed melasma on both cheeks received 2 MFU‐V treatments spaced 1 month apart. At monthly visits over 5 months, treatment efficacy and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…TEWL can be used to evaluate skin barrier function. TEWL on the combined side decreased from 17 (14,22) to 14 (12,16) (g/m²/h) (p within = 0.018), while on the MFU side, TEWL decreased from 17.1 (14.8, 19.4) to 14.8 (12.4, 19.4) (g/m²/h) (p within = 0.079). This demonstrated that the combined side has a better effect in repairing the skin barrier (p between = 0.028).…”
Section: Improvement Of Skin Tonementioning
confidence: 89%
See 2 more Smart Citations
“…TEWL can be used to evaluate skin barrier function. TEWL on the combined side decreased from 17 (14,22) to 14 (12,16) (g/m²/h) (p within = 0.018), while on the MFU side, TEWL decreased from 17.1 (14.8, 19.4) to 14.8 (12.4, 19.4) (g/m²/h) (p within = 0.079). This demonstrated that the combined side has a better effect in repairing the skin barrier (p between = 0.028).…”
Section: Improvement Of Skin Tonementioning
confidence: 89%
“…This may be due to the vibrations and friction caused by ultrasound during propagation, which can mechanically disrupt or eliminate melanin and pigment fragments above the TIZs plane. [15][16][17] The pigments and pigment fragments produced during this process may recruit macrophages, triggering a response similar to laser tattoo removal, promoting pigment and epidermal metabolism. 18 Although more gentle and slow than tattoo removal, this process can still enhance skin tone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation